Challenges and strategies in implementing kangaroo mother care across Indonesia: a literature review - Gunawan, Rendi Prawira; Edhy, Anky Tri Rini Kusumaning; Tehuteru, Edi Setiawan; Widnyana, Anak Agung Ngurah Ketut Putra; Rustina, Yeny; Tobing, Hesti Kristina P (Indonesian Journal of Perinatology, 2025)
Kangaroo Mother Care (KMC) is a simple and low-cost intervention proven effective in reducing morbidity and mortality among low birth weight (LBW) infants through skin-to-skin contact, exclusive breastfeeding, and post-discharge monitoring. KMC plays an essential role in maintaining the infant’s body temperature, enhancing physiological stability, improving the sucking reflex, accelerating weight gain, and strengthening the emotional bond between mother and baby. In Indonesia, KMC has been integrated into national health policy since 2009 through the “Mother and Baby Friendly Hospital Program,” yet its implementation still faces several challenges, including limited facilities, inadequate health worker training, and insufficient family support. Studies conducted at the hospital and primary care levels have demonstrated positive outcomes in terms of growth, physiological stability, and breastfeeding success among LBW infants who received KMC. The main barriers of KMC implementation in Indonesia are found at the maternal and family level, the healthcare provider and facility level, and also the social-cultural and economic level. Multistage efforts, such as developing legal frameworks, training, teamwork, utilizing the available resources, communication, supervision, documentation, and evaluation, may overcome the barriers and increase the KMC implementation in Indonesia.